Effects of eucalyptus on soil properties and litter decomposition processes - Sarker, Protika; Kashem, Md Abul; Ahmed, Ashfaque; Hoque, Sirajul; Hossain, Mohammad Zabed (Dhaka University Journal of Biological Sciences, 2022)
This study investigated the effect of plantation of exotic species Eucalyptus (Eucalyptus spp.) on the physico-chemical properties of soil by collecting field data and also on litter decomposition and nitrogen mineralization rates of the other selected species by following microcosm experimental design. Effects of Eucalyptus plantation on soil properties were studied by comparing soil properties of plots planted with Eucalyptus and other two species Acacia (Acacia auriculiformis A. Cunn. ex Benth.) and Lagerstroemia (Lagerstroemia speciosa (L.) Pers.) located at Madhupur, Tangail and Singra, Dinajpur, respectively. Effects of Eucalyptus litter on decomposition and nitrogen mineralization rates of litter of Axonopus (Axonopus compressus (Sw.) P. Beauv), Swietenia (Swietenia mahagoni (L.) Jacq.) and Teak (Tectona grandis L.f.) were studied by incubating leaf litter of these species with that of Eucalyptus at room temperature for 12 months. Results showed that soil moisture content was significantly lower in plot planted with Eucalyptus than that with Lagerstroemia. However, no significant difference appeared when soil moisture content was compared between Eucalyptus and Acacia indicating that plantation effects varied with the identity of species. Soil pH, total P (%) and organic C (%) contents were significantly lower in plots planted with Eucalyptus. Although mixing of leaf litter of Eucalyptus with that of A. compressus, S. mahagoni and T. grandis did not affect significantly, it affected mass loss rate of these three plant species significantly and such effect could be explained by the chemical composition of the litter used in the incubation study. Overall, the results of the present study indicated that plantation with Eucalyptus might have potential influence on altering soil properties and litter decomposition of other plant species, nevertheless, such effects varied with the species with whom the comparison was made. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 443-452, 2022 (June)